2008
DOI: 10.1002/ceat.200800457
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Screening for the Design and Optimization of Chromatographic Processes: Assessment of Model Parameter Determination from High Throughput Compatible Data

Abstract: Chromatographic processes can be optimized in various ways, and the two most prominent approaches are based either on statistical data analysis or on experimentally validated simulation models. Both strategies rely heavily on experimental data, the generation of which usually imposes a significant bottleneck on rational process design. The latter approach is followed in this work, and the utilizability of high throughput compatible experiments for the determination of model parameters which are required for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Susanto (2008) highlights the importance of having better judgment on individual change readiness perception prior to any change implementation. A good assessment of employee change readiness would help change agents, business consultants and management to understand the gap between their own expectation about the change and the change recipients' anticipation of the change (Ghany, 2014).…”
Section: Employee Readinessmentioning
confidence: 99%
“…Susanto (2008) highlights the importance of having better judgment on individual change readiness perception prior to any change implementation. A good assessment of employee change readiness would help change agents, business consultants and management to understand the gap between their own expectation about the change and the change recipients' anticipation of the change (Ghany, 2014).…”
Section: Employee Readinessmentioning
confidence: 99%
“…Optimizations of preparative chromatographic processes are frequently based on experimentally validated simulation models. This strategy requires a large amount of experimental data, and their generation imposes a significant bottleneck on rational process design [30]. Susanto et al [30], Charlton et al [31], and Coffman et al [32] have demonstrated that high-throughput screening can be a rapid way to acquire these data.…”
Section: Process Optimizationmentioning
confidence: 99%
“…This strategy requires a large amount of experimental data, and their generation imposes a significant bottleneck on rational process design [30]. Susanto et al [30], Charlton et al [31], and Coffman et al [32] have demonstrated that high-throughput screening can be a rapid way to acquire these data. Those studies used different columns with bed volumes between 0.1 and 1 mL that were installed into a 96-well microplate.…”
Section: Process Optimizationmentioning
confidence: 99%
“…A similar carrier is available under the name Te-Chrom (Tecan). A thorough description of parallelized chromatography performed automated on a LHS has been published by Wiendahl et al (2008) and Susanto et al (2008). Further, the LHS was equipped with an Infinite 200 plate reader (Tecan) to measure the mid-UV spectra of the calibration and validation samples as well as the chromatographic fractions.…”
Section: Liquid Handling Stationmentioning
confidence: 99%
“…From column experiments, information on dynamic binding capacities and chromatographic resolution can be derived. Both batch and column chromatography in HTE mode can also be used to determine parameters for mechanistic modeling of chromatographic processes (Susanto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%